Penambahan Tepung Ikan Lele (Clarias Gariepinus) Dan BMC Tempe Terhadap Karakteristik Cookies - Kiswati; Ida Prijatni (Akademi Kebidanan Aifa Husada Madura, 2023)
The number of toddlers in Jember whose height and weight do not match their age is quite large. The number reached 20,000 children or 17% of the total toddlers in Jember. Overall, the range is 17% or about 20,000 toddlers in Jember who are stunted and the highest number is in Jelbuk sub-district 493 toddlers, Ledokombo reaches 178 toddlers (25.8%). In the Patrang area there are about 22 stunted toddlers. The purpose of the study was to determine the addition of dumbo catfish meat flour [clarias garepinus] to the physical, chemical, and sensory characteristics of BMC Tempe cookies. This research is a pure experiment with a Completely Randomized Design (CRD) design. There are 4 variations of catfish flour substitution formula and BMC Tempe flour in making cookies. While organoleptic tests were carried out in the bintoro village area, tests of carbohydrate, protein, fat and calcium levels at the University Health Laboratory Dr. Soebandi Jember. Respondents in this study were untrained respondents, namely parents and children totaling 30 people. The assessment was done in the form of acceptability assessment and calculation of carbohydrate, protein, fat content. Acceptability assessment (color, aroma, texture, and taste) by untrained respondents used a questionnaire, while the calculation of carbohydrate, protein, fat and calcium levels was calculated based on nutrient content tests. The results of the acceptability test were processed and analyzed to determine the high acceptability. Kruskal Wallis test (α=0.05) was used to determine the difference in acceptability of cookies with substitution of catfish flour and BMC tempe flour. Statistical tests using Kruskal Wallis obtained the results of H0 rejected and Ha accepted where the asymp.sig value <0.05 which means there are differences in organoleptic tests both color, texture, aroma and taste of cookies made from a mixture of tempeh, mung beans, rice and catfish flour.